Comprehensive review on carotenoid composition: Transformations during processing and storage of foods - Meléndez Martínez, Antonio J. (2023)
Stimulated by their multifaceted functions and actions, carotenoids have been among the most investigated food components, producing a voluminous, complicated, and sometimes inconsistent literature. This review puts into context developments in the last decade to have a comprehensive current knowledge on these valuable food constituents. Carotenoid analysis continues to show the wide biodiversity of carotenogenic foods and the many factors that affect the composition. Because of their instability, subject to multiple influencing factors, retention of carotenoids during processing and storage of food has been a daunting task. Since thermal processing may result in substantial carotenoid losses, thermal processes that are much faster than the conventional methods and nonthermal processing have been introduced. The processing conditions of nonthermal processing should, however, be well established so that microbial and enzymatic inactivation is achieved while maintaining nutrients and bioactive compounds. Instead of losses, higher carotenoid levels and bioaccessibility are sometimes reported for both thermal and nonthermal processing, attributed to greater extractability of carotenoids during analysis and greater release from the food matrix during digestion. Carotenoids differ markedly in their susceptibility to degradation, the epoxycarotenoids being most degradable. Results are mixed, however, in relation to the comparative stability of hydroxycarotenoids and carotenes. E-Z isomerization at sterically unhindered double bonds is now well documented. There is also more information about oxidative degradation, although more work is needed on this topic. It consists of epoxidation, cleavage to apocarotenoids and finally fragmention to low mass compounds. Enzymatic and non-enzymatic cleavage of carotenoids forms important aroma compounds but can also produce off-flavor.